2020
DOI: 10.22610/jebs.v12i2(j).3022
|View full text |Cite
|
Sign up to set email alerts
|

Financial Performance in Indonesian Companies: The Role of Environmental Performance and Environmental Disclosure

Abstract: The aim of this study is to acquire empirical evidence that environmental performance and environmental disclosure has an influence on financial performance. The key differentiation between this study and previous studies is the use of different variables and measurement methods. The hypothesis of this study is based on stakeholder theory and legitimation theory. The purposive sampling method was used to collect data from manufacture companies listed in the Indonesian Stock Exchange and the PROPER 2016-2018 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This result is in line with the studies byDerila et al (2020),Ismail (2021),Lastiningsih et al (2020),Nakao et al (2006) andGull et al (2022), who found the same results significant relationship with the financial performance of the firms. The panel data analysis presented in the SOCL Model aims to explore the impact of Social performance on Return on Assets (ROA) in a sample of 2153 observations.…”
supporting
confidence: 92%
“…This result is in line with the studies byDerila et al (2020),Ismail (2021),Lastiningsih et al (2020),Nakao et al (2006) andGull et al (2022), who found the same results significant relationship with the financial performance of the firms. The panel data analysis presented in the SOCL Model aims to explore the impact of Social performance on Return on Assets (ROA) in a sample of 2153 observations.…”
supporting
confidence: 92%
“…Environmental Performance: Environmental performance is a company system that is willing to integrate environmental attention and awareness of company operations and interactions with stakeholders that go beyond the legal responsibility of the organization (Lastiningsih and Aswar, 2020). Environmental performance is very important for the company.…”
Section: Stakeholders Theorymentioning
confidence: 99%
“…Using PROPER which was proclaimed by the Ministry of Environment which aims to disseminate information related to environmental performance and to increase the level of company performance improvement (Lastiningsih and Aswar, 2020). If the company pays close attention to environmental performance, the company has implemented CSR as there is evidence of the company's high attention to environmental and social concerns (Halmawati and Oktalia, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to (Fahmi, 2012) In (Lastiningsih, 2020) financial performance to analyze and study the company in implementing and the following implementation correctly, the usage of the financial records of the organization concerned and the financial data is reflected in the financial statements. According to (Muhammad, 2015), (Qi, 2014), (Kucukbay, 2016) say agree that environmental performance can affect financial performance.…”
Section: Financial Performancementioning
confidence: 99%
“…But in measuring financial performance not only focuses on generating large profits for the company but also must have an ethical attitude in carrying out financial performance. According to (Gatimbu, 2016) In (Lastiningsih, 2020) said that there is increased awareness about how to do methods to improve long-term financial performance as can be done by using financial statement analysis using financial ratios.…”
Section: Introductionmentioning
confidence: 99%